Design and Implementation of Salary Slip Application with WhatsApp-based Distribution - Alfarizky, Fakhruri; Bukhori, Iksan; Rahadiyan, Deffa (President University, 2024)
Abstract- XYZ Company is a company engaged in services. The first problem is the security of pay slip data. Currently, pay slips are made based on Microsoft Excel data that can be accessed by anyone, even if the person concerned is not an authorized officer. The next problem is the timing of payroll. XYZ Company supplies employees to 18 companies. Thus, the timing of employee payroll is different from one another, depending on the company where the employee works. Currently, payroll is divided into several different dates, namely on the 25th, 30th, 5th and 10th of each month. After the payroll process is complete, it is followed by making pay slips and distributing the pay slips. Making and distributing pay slips is inefficient if done using conventional methods. In this research, an automatic salary generation and distribution system is built using a Python-based program as a programming container, JasperReports as an automatic salary slip report generation and WhatsApp as a medium for distributing salary slips. Based on the results of the tests that have been carried out, the application built can reduce the processing time for 1 person by 47 seconds or 71.64% to 4 people by 4 minutes 24 seconds or 93.27%. The more payslips that are created and distributed, the greater the time savings. This shows that the automatic system application is more efficient in making and distributing pay slips than conventional methods.Â The application made also has a security feature where the application can only be accessed by users, the system cannot be accessed if the user does not have a username and password.